Students' Ability to Understand Concepts in Solving Problems of Similarity and Congruence - Seko, Herbert; Nahak, Selestina; Simarmata, Justin Eduardo; Atencia, Bryant Bennet D (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study employs a qualitative descriptive approach aimed at evaluating students' conceptual understanding in solving similarity and congruence problems at SMP Negeri Oelneke. The subjects of the study were ninth-grade students. The results of the conceptual understanding test show that 29.4% of the students fall into the low ability category, 41.1% into the moderate ability category, and 29.4% into the high ability category. These results indicate that the majority of students at SMP Negeri Oelneke demonstrate a moderate level of conceptual understanding. The students face difficulties in solving the problems due to a lack of understanding of the given problems, which prevents them from providing optimal responses.